Sum of the Given Series (4)

Calculus Level 3

n = 1 1 n 2 ( n + 1 ) 2 = π A B C \large\sum_{n=1}^\infty\frac 1{n^2(n+1)^2}=\frac {\pi^A}B-C

where A , B A,B and C C are integers. Find A + B + C . A+B+C.


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
May 21, 2018

S = n = 1 1 n 2 ( n + 1 ) 2 By partial fraction decomposition = n = 1 ( 2 n + 2 n + 1 + 1 n 2 + 1 ( n + 1 ) 2 ) (see note) = 2 + n = 1 1 n 2 + n = 1 1 ( n + 1 ) 2 = 2 + n = 1 1 n 2 + n = 1 1 n 2 1 = 2 n = 1 1 n 2 3 = 2 ζ ( 2 ) 3 where ζ ( n ) = k = 1 1 k n is Riemann = π 2 3 3 zeta function and ζ ( 2 ) = π 2 6 . \begin{aligned} S & = \sum_{n=1}^\infty \frac 1{n^2(n+1)^2} & \small \color{#3D99F6} \text{By partial fraction decomposition} \\ & = \sum_{n=1}^\infty \left(- \frac 2n + \frac 2{n+1} + \frac 1{n^2} + \frac 1{(n+1)^2} \right) & \small \color{#3D99F6} \text{(see note)} \\ & = - 2 + \sum_{n=1}^\infty \frac 1{n^2} + \sum_{n=1}^\infty \frac 1{(n+1)^2} \\ & = -2 + \sum_{n=1}^\infty \frac 1{n^2} + \sum_{n=1}^\infty \frac 1{n^2} - 1 \\ & = 2 \sum_{n=1}^\infty \frac 1{n^2} - 3 \\ & = 2 {\color{#3D99F6}\zeta(2)} - 3 & \small \color{#3D99F6} \text{where }\zeta (n) = \sum_{k=1}^\infty \frac 1{k^n} \text{ is Riemann} \\ & = \frac {\pi^2}3 - 3 & \small \color{#3D99F6} \text{zeta function and }\zeta (2) = \frac {\pi^2}6. \end{aligned}

Therefore, A + B + C = 2 + 3 + 3 = 8 A+B+C=2+3+3=\boxed{8} .


Note: Let 1 n 2 ( n + 1 ) 2 = A n + B n + 1 + C n 2 + D ( n + 1 ) 2 \frac 1{n^2(n+1)^2} = \frac An + \frac B{n+1} + \frac C{n^2} + \frac D{(n+1)^2} . Multiplying both sides by n 2 ( n + 1 ) 2 n^2(n+1)^2 :

A n ( n + 1 ) 2 + B n 2 ( n + 1 ) + C ( n + 1 ) 2 + D n 2 = 1 Putting n = 0 C = 1 Putting n = 1 D = 1 Putting n = 1 2 A + B = 2 Putting n = 2 3 A + 2 B = 2 A = 2 B = 2 \small \begin{aligned} An(n+1)^2 + Bn^2(n+1) + C(n+1)^2 + Dn^2 & = 1 & \color{#3D99F6} \text{Putting }n=0 \\ \implies C & = 1 & \color{#3D99F6} \text{Putting }n=-1 \\ \implies D & = 1 & \color{#3D99F6} \text{Putting }n=1 \\ \implies 2A+B & = -2 & \color{#3D99F6} \text{Putting }n=2 \\ \implies 3A+2B & = -2 \\ \implies A = -2 \implies B & = 2 \end{aligned}

Naren Bhandari
May 21, 2018

S = n = 1 1 n 2 ( n + 1 ) 2 = n = 1 ( 1 n ( n + 1 ) ) 2 see OR S = n = 1 ( 1 n 2 2 ( 1 n 1 n + 1 ) telescoping sum + 1 ( n + 1 ) 2 partial fraction decomposition ) S = π 2 6 2 + π 2 6 1 = π 2 3 3 S= \sum_{n=1}^{\infty} \dfrac{1}{n^2(n+1)^2} =\sum_{n=1}^{\infty}\left(\dfrac{1}{n(n+1)}\right)^2 \qquad {\color{#3D99F6}\text{see OR}}\\ S =\sum_{n=1}^{\infty} \left(\underbrace{\dfrac{1}{n^2} -\overbrace{2\left( \dfrac{1}{n}-\dfrac{1}{n+1} \right)}^{\text{telescoping sum}}+\dfrac{1}{(n+1)^2}}_{\text{partial fraction decomposition}}\right) \\S = \dfrac{\pi^2}{6}- 2 +\dfrac{\pi^2}{6} - 1 =\boxed{ \dfrac{\pi^2}{3} -3} \

Hence, A + B + C = 2 + 3 + 3 = 8 A+B+C = 2+3+3 =8


OR S = n = 1 ( 1 n ( n + 1 ) ) 2 = n = 1 ( 1 n 1 n + 1 ) 2 = 1 n 2 2 n ( n + 1 ) + 1 ( n + 1 ) 2 S=\sum_{n=1}^{\infty}\left(\dfrac{1}{n(n+1)}\right)^2 = \sum_{n=1}^{\infty} \left(\dfrac{1}{n} -\dfrac{1}{n+1}\right)^2 = \dfrac{1}{n^2} -\dfrac{2}{n(n+1)} +\dfrac{1}{(n+1)^2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...